Numerical Simulation on the Diffusion of Alien Phytoplankton in Bohai Bay - Zhang, Beibei; Pu, Amin; Jia, Peng; Xu, Chenglong; Wang, Qinggai; Tang, Wenhao (Frontiers in Ecology and Evolution, 2021)
In order to investigate the motion feature of alien phytoplankton in the Bohai Bay area, this manuscript builds a two-dimensional tide hydrodynamic model coupled with a particle tracking model to simulate the alien phytoplankton movement trajectory and the diffusion processes with different specific growth rates in three major ports of Bohai Bay (Caofeidian port, Tianjin port, and Huanghua port). The results show that the movement of alien phytoplankton is mainly affected by the tidal circulation near the port, and the diffusion trend is basically consistent with the residual flow in Bohai Bay. The distribution density of alien phytoplankton is directly affected by the specific growth rate of the population and is positively related to specific growth rate. The released alien phytoplankton in the three major ports are all concentrated around the ports area. The largest distribution density is in Tianjin port, and the possibility of red tide disasters is also greatest here compared with the other two major ports. It is necessary to strengthen the monitoring of alien organisms in the port area and actively prevent alien phytoplankton from entering Bohai Bay through ship ballast water.